2012
DOI: 10.1002/eji.201142140
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐specific glycoprotein 1a activates dendritic cells to provide signals for Th17‐, Th2‐, and Treg‐cell polarization

Abstract: Because of their plasticity and central role in orchestrating immunity and tolerance, DCs can respond to pregnancy-specific signals, thus promoting the appropriate immune response in order to support pregnancy. Here, we show that pregnancy-specific glycoprotein (PSG1a), the major variant of PSG released into the circulation during pregnancy, targets DCs to differentiate into a subset with a unique phenotype and function. This semimature phenotype is able to secrete IL-6 and TGF-β. PSG1a also affected the matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 50 publications
5
51
0
Order By: Relevance
“…1). Pregnancyspecific glycoprotein promotes the expansion of IL-5-secreting cells in vivo, which is related with a successful pregnancy (Martínez et al, 2012). It is reported that dendritic cells treated with placental growth factor results in the suppression of naïve CD 4+ T cell proliferation, with an upregulation of IL-5 secretion in the CD 4+ T cell, which is beneficial for pregnancy in human (Lin et al, 2007).…”
Section: Resultsmentioning
confidence: 98%
“…1). Pregnancyspecific glycoprotein promotes the expansion of IL-5-secreting cells in vivo, which is related with a successful pregnancy (Martínez et al, 2012). It is reported that dendritic cells treated with placental growth factor results in the suppression of naïve CD 4+ T cell proliferation, with an upregulation of IL-5 secretion in the CD 4+ T cell, which is beneficial for pregnancy in human (Lin et al, 2007).…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, potent tolerance mechanisms are required to prevent destruction of fetal cells. As PSGs have the capacity to modulate maternal immune responses (Martinez et al 2012, 2013, Falcon et al 2014, we previously suggested that maintenance of immune tolerance is an important selective force in the expansion of PSG gene clusters (Kammerer & Zimmermann 2010). The horse has, similar to swine and cattle, an epitheliochorial placenta in which fetal cells are separated from the maternal immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to what is reported for Gal-1 54 and HO-1 27 among others, PSG1a seems to modulate DC phenotype and maturation that finally promotes the secretion of IL-17. 84 Other PSGs are also of relevance for establishment of pregnancy as elegantly demonstrated by the group of Gabriela Dveksler. 85,86 …”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 95%